2021
DOI: 10.1155/2021/6689212
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Local Scour and Related Mechanical Effects at River‐Crossing Underwater Oil and Gas Pipelines

Abstract: Among the various geological disasters that threaten the safe operation of long-distance oil and gas pipelines, water-damage disasters are numerous and widely developed. Especially the pipelines crossing river channels or gullies are vulnerable to scouring hazards from storms and floods. A water-damage disaster physical model was established to investigate the characteristics of the riverbed scour profile and the pipeline force when the pipeline was buried at different depths under the condition of different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In reference [17], researchers have studied the local scouring process of semi-buried pipelines in sandy riverbeds through experiments. The test results show that the scouring process can be divided into a start-up stage, micropore formation stage, extension stage, and equilibrium stage.…”
Section: Analysis Of Local Scouring Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In reference [17], researchers have studied the local scouring process of semi-buried pipelines in sandy riverbeds through experiments. The test results show that the scouring process can be divided into a start-up stage, micropore formation stage, extension stage, and equilibrium stage.…”
Section: Analysis Of Local Scouring Processmentioning
confidence: 99%
“…In 2021, Huang [16] carried out two-dimensional numerical simulations to investigate the scour beneath a single pipeline and piggyback pipelines subjected to an oscillatory flow condition at a KC number of 11 and captured typical steady-streaming structures around the pipelines due to the oscillatory flow condition. In 2021, Cui [17] investigated the characteristics of the riverbed scour profile for a pipeline buried at different depths under the condition of riverbed sediments with different particle sizes. The results indicated that, in general, the equilibrium scour depth changed in a spoon shape with the gradual increase in the embedment ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al [9] investigated the local scour of pipelines on slopes under regular wave action, finding that the depth and width of erosion exhibit two stages with time. Subsequently, relevant scholars discussed local scour time around pipelines in different seabed soils, analyzing relevant influencing factors [10,11]. Sumer et al [12] studied the erosion process of circular structures in three types of seabed soil under wave action through experimental methods, finding that the sandy soil layer had the shortest erosion time.…”
Section: Introductionmentioning
confidence: 99%